1989
DOI: 10.1017/s0003356100003883
|View full text |Cite
|
Sign up to set email alerts
|

Effect of restricted food intake, before and/or after mating, on the reproductive performance of Greyface ewes

Abstract: The effect on the reproductive performance of Greyface (Border Leicester x Scottish Blackface) ewes of a low level food intake and associated loss of live weight from either 14 days before mating, or from the time of mating, until 11 to 26 days after mating, was investigated. Ewes (252) were allocated to one of three treatments with ewes within each treatment divided into two flocks (flock A: 16 ewes per treatment; flock B: 68 ewes per treatment). Ewes of treatment LL were given a ration providing proportionat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1
4

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 12 publications
(13 reference statements)
4
25
1
4
Order By: Relevance
“…Opposite to the observations of this experiment, Rhind et al (1989), Lozano et al (1998) and O'Callanghan et al (2000) observed difference in the blood progesterone concentration in ewes subjected to different feeding programs. However, in these studies, ewes presenting lower blood progesterone concentration ingested twice to four times more ME than those with higher concentration of this hormone.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Opposite to the observations of this experiment, Rhind et al (1989), Lozano et al (1998) and O'Callanghan et al (2000) observed difference in the blood progesterone concentration in ewes subjected to different feeding programs. However, in these studies, ewes presenting lower blood progesterone concentration ingested twice to four times more ME than those with higher concentration of this hormone.…”
Section: Resultscontrasting
confidence: 73%
“…A nutritional strategy that may be used to enhance ovulation rate and, consequently, prolificacy, is overfeeding or flushing, which consists in increasing nutrition levels in ewes before mating. The effects of overfeeding with high-energy diets are well known (Rhind et al, 1989;Viñoles et al, 2008); however, few studies have verified this with protein-rich feeds. Some authors have demonstrated that overfeeding with protein feeds increased ovulation rate (Molle et al, , 1997, while the same variable was unaltered by overfeeding with proteins of different degradability (Branca et al, 2000;Saunders et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Embora os efeitos da sobrealimentação com dietas ricas em energia sejam bem documentados (Rhind et al, 1989;Vinõles et al, 2008), as informações relativas à sobrealimentação com alimentos proteicos são escassas. Molle et al (1997) observaram maior número de ovulações em ovelhas da raça Sarda sob sobrealimentação com 270 g de farelo de soja/dia a partir de 14 dias antes até dois dias após a monta, do que em ovelhas não suplementadas (1,8 vs 1,3 corpos lúteos, respectivamente).…”
Section: Introductionunclassified
“…It is known that nutritional status of ewes around the mating period alters ovarian activity and lambing rates after mating in many sheep breeds (Lassoued et al, 2004). Low feed intake before mating reduces the mean ovulation rate and inadequate nutrition after mating induces a higher rate of ova wastage (Rhind et al, 1989). Moreover, over-feeding during early gestation reduces pregnancy rate and reproductive performance (Parr et al, 1987).…”
Section: Introductionmentioning
confidence: 99%